2019
DOI: 10.4102/sajhrm.v17i0.1080
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the antecedents and consequences of employee satisfaction for urban and rural healthcare workers in KwaZulu-Natal province, South Africa

Abstract: Orientation: The South African healthcare industry is facing significant challenges to retain quality healthcare professionals to deliver services in rural areas.Research purpose: The main purpose of this study was to compare the antecedents and consequences of employee satisfaction for healthcare professionals in urban and rural areas to establish if there are distinguishing factors that can better inform human resource (HR) management to improve job satisfaction and service delivery. KwaZulu-Natal province w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The employee profile factor is made up of a combination of employee investment factors and non-work-related factors. Tawana et al identified that the length of time that an employee intends to stay at the organization, a job tenure, redefines the intention of that employee to leave [25]. This is referred to as the employee investment which means the perception employees have about the length of time they would like to spend with the organization at the time of hiring.…”
Section: Factors Impacting Employee Turnovermentioning
confidence: 99%
“…The employee profile factor is made up of a combination of employee investment factors and non-work-related factors. Tawana et al identified that the length of time that an employee intends to stay at the organization, a job tenure, redefines the intention of that employee to leave [25]. This is referred to as the employee investment which means the perception employees have about the length of time they would like to spend with the organization at the time of hiring.…”
Section: Factors Impacting Employee Turnovermentioning
confidence: 99%